The Role of Postoperative Bisphosphonates Therapy in Union Time and Functional Outcome in Intertrochanteric Fracture of Femur - Khan, Nazir; Pradhan, Rabindra Lal; Pandey, Bimal Kumar; Khanal, Krishna Raj; Rijal, Kiran Prashad; Manandhar, Rajeev Raj; Sharma, Sashmit (Nepal Orthopaedic Association Journal, 2021)
Background: Intertrochanteric fracture of femur is one of the commonest injuries sustained by elderly people. It comprise approximately half of all hip fractures caused by low energy trauma in elderly population while in case of younger patients, it is due to high energy trauma. At present, surgical fixation of fracture is the primary treatment for intertrochanteric fractures. However, many studies have shown that anti-osteoporosis therapy like bisphosphonates may be better for postoperative rehabilitation, functional outcome and long-term survival. We analyzed the clinical results of bisphosphonate therapy in surgically treated intertrochanteric fractures.Method: A Prospective comparative hospital based clinical study was conducted at Department of Orthopedic Surgery, Kathmandu Medical College Teaching Hospital from January 2018 to July 2019. A total of 36 patients (14 male and 22 female) with surgically treated intertrochanteric fracture of femur were enrolled. Patients were randomly divided into study or control groups (18 cases in each group) according to the even or odd date of admission as per Nepali calendar. Patients in both groups were treated by proximal femoral nail (PFN). In the study group, patients received 5 mg zoledronic acid intravenously on 3rd postoperative day. The functional outcome and union was evaluated at 3 weeks, 6 weeks, 3 months and 6 months with Harris hip score and RUSH score.Result: Fracture healed more quickly in patients treated with zoledronic acids than those in control group [(12.77 ± 1.89) vs (15.86 ± 0.94) weeks, p=0.040]. No significant differences were found between the two groups in regard of HHS scores at any period of follow-up. The RUSH score of the patient in between two groups at 3 months follow-up [(23.16 ± 0.85) vs (20.33 ± 3.32), p=0.000] and 6 months follow-up [(29.11 ± 1.23) vs (26.88 ± 2.51), p=0.002] were statistically significant. Two cases of influenza like symptoms in study groups but no other major complications.Conclusion: Zoledronic acid injection is a safe and effective treatment option for the elderly patients with osteoporotic intertrochanteric fracture who are treated surgically. It can improve functional outcome and promote earlier fracture healing with few complication.